Kepemimpinan Visioner Kepala Sekolah A Literature Review - Wahyuni, Apri; Hariri, Hasan (Program Studi Magister Manajemen Pendidikan, 2023)
Abstract: Principal Visionary Leadership This study aims to explore the effect of the principal's visionary leadership and teacher discipline on teacher performance in schools. The results of the study show that the principal's visionary leadership and teacher discipline have a significant influence on teacher performance, and both affect teacher performance together. Principals have an important role in leading and optimizing resources in schools to achieve common goals, while teacher discipline helps create a healthy and professional work environment. Although the No Child Left Behind law does not explicitly mention the role of the school principal in improving school progress, the results of this study show that school principals have an important role in improving teacher performance and the progress of educational institutions.Keywords: academic, principal, visionaryDOI: 10.23960/jmmp .v11.i1.2023.04